2022
DOI: 10.3390/bios12100784
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoresis: An Approach to Increase Sensitivity, Reduce Response Time and to Suppress Nonspecific Binding in Biosensors?

Abstract: The performance of receptor-based biosensors is often limited by either diffusion of the analyte causing unreasonable long assay times or a lack of specificity limiting the sensitivity due to the noise of nonspecific binding. Alternating current (AC) electrokinetics and its effect on biosensing is an increasing field of research dedicated to address this issue and can improve mass transfer of the analyte by electrothermal effects, electroosmosis, or dielectrophoresis (DEP). Accordingly, several works have show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 140 publications
0
2
0
Order By: Relevance
“…When applied to proteins, their relatively small size, R 0 ∼ 1 nm, yields a force too low to trap a protein at the practical field strength E ≤ 100 kV/cm. [9][10][11][12] Nevertheless, Washizu et al demonstrated protein trapping with fields E ∼ 10 kV/cm, an order of magnitude smaller than expected. 13 This observation had remained puzzling 14 until it was recognized that a large intrinsic permanent dipole moment of a protein produces an induced dipole M 0 E nearly four orders of magnitude higher than what follows for the induced dipole from the CM factor.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…When applied to proteins, their relatively small size, R 0 ∼ 1 nm, yields a force too low to trap a protein at the practical field strength E ≤ 100 kV/cm. [9][10][11][12] Nevertheless, Washizu et al demonstrated protein trapping with fields E ∼ 10 kV/cm, an order of magnitude smaller than expected. 13 This observation had remained puzzling 14 until it was recognized that a large intrinsic permanent dipole moment of a protein produces an induced dipole M 0 E nearly four orders of magnitude higher than what follows for the induced dipole from the CM factor.…”
Section: Introductionmentioning
confidence: 89%
“…This theoretical prediction opened the door to applications of DEP to protein trapping and a number of potential systems where such effects can be realized have been identified. 6,12,[16][17][18][19][20][21] It is now increasingly appreciated that DEP susceptibilities of proteins are mostly consistent between different reports 6,19,22 and do not follow dielectric predictions based on the CM factor. [22][23][24][25] The electric field magnitude required for trapping the protein can be estimated by a balancing condition equating the magnitude of the free energy |F E | to the thermal kinetic energy of the particle: 6,13,26 (3/2)k B T .…”
Section: Introductionmentioning
confidence: 99%